Frequency Of Oral Findings With Reference To Diabetes Mellitus Patients: A Multi-center Cross-sectional Study - Muhammad Shahrukh Khan Sadiq; Moona Mumtaz; Syed Abrar Ali; Jouhrah Hussain Khan; , Syed Ahmed Omer; Zahra Karim; Daud Mirza (Journal of Bahria University Medical and Dental College)
Objective: